The choice of auxiliary substances to obtain sublingual glycin tablets with thiotriazoline with direct compaction method Reporting 1. Study of the influence of excipients on the bulk density, the bulk density after shrinkage, the fluidity and the angle o - L. I. Kucherenko; O. V. Khromylova; H. R. Nimenko; Z. B. Moriak (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Today in Ukraine, stroke remains the second and most common cause of premature mortality and disability. More than 111.000 new cases of stroke occur every year in Ukraine. This is a very topical medical and social problem worldwide. Today, a promising area of primary neuroprotection in cerebral ischemia is to correct the imbalance of excitatory and inhibitory neurotransmitter systems through the activation of natural inhibitory processes. Our attention was drawn to the natural inhibitory neurotransmitter glycine and its role in the mechanisms of acute cerebral ischemia. There is evidence of the ability of the thiotriazoline antioxidant to potentiate the therapeutic effect of neurometabolic cerebroprotectors. Based on this, we have created a new combination drug based on glycine with thiotriazoline. For the new combination drug, a rational dosage form of the tablet was selected.